Measuring the Effectiveness of Interpersonal Psychotherapy Training for Kerman Prison Staff: With Emphasis on Prisoners' Rights - Ataallah Salehi; mohsen saeedi; Ayda Bana Hossein pour; NAIMA MOHAMMADI (توسعه اجتماعی)
This study aimed at improving the rights of prisoners by measuring the effectiveness of providing interpersonal psychotherapy training to social workers and psychologists in Kerman Central Prison. This experimental study uses focus groups, the Standard Interpersonal Problems Questionnaire (IIP) and Beck Depression Inventory and Alexithymia Toronto Scale (TAS), to assess the knowledge and skills of prison staff regarding how to deal with prisoners. Interpersonal psychotherapy training program (IPT) was performed using pre-test and post-test methods for 39 social workers and psychologists working in Kerman Prisons Organization who participated in interpersonal psychotherapy training workshops. All participants were included in this study and the data were analyzed using SPSS 22 software. The findings showed that the effectiveness of interpersonal psychotherapy training in the post-test phase is a function of participants' scores of depression, mood disorders and problems. Less interpersonal problems, mood swings, and depression among prison staff meant greater effectiveness of the prisoner training program. The research findings also showed that the higher level of education and work experience of paramedics increased the effectiveness of the training program. Therefore, it is suggested that the Prisons Organization, with the help of human rights experts and social psychologists, improve the ability of its personnel regarding their interpersonal communication and reduce depression, which makes it possible for this group to decrease the communicative problems of the prisoners.